2012
DOI: 10.1093/neuonc/nos089
|View full text |Cite
|
Sign up to set email alerts
|

miR-181d: a predictive glioblastoma biomarker that downregulates MGMT expression

Abstract: Genome-wide microRNA (miRNA) profiling of 82 glioblastomas demonstrated that miR-181d was inversely associated with patient overall survival after correcting for age, Karnofsky performance status, extent of resection, and temozolomide (TMZ) treatment. This association was validated using the Cancer Genome Atlas (TCGA) dataset (n= 424) and an independent cohort (n= 35). In these independent cohorts, an association of miR-181d with survival was evident in patients who underwent TMZ treatment but was not observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
153
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(164 citation statements)
references
References 17 publications
8
153
1
2
Order By: Relevance
“…Recent studies addressed a further level of MGMT regulation through direct binding of specific miRNAs to the 3'-UTR of MGMT transcripts, which may lead to decreased mRNA stability and/or reduced protein translation [47]. Distinct miRNAs that have been implicated as direct regulators of MGMT expression include miR-181b [48,49], miR-181d [49], mir221/222 [50], as well as miR-767-3p and miR-648 [47]. Thus, also aberrant expression of miRNAs may contribute to the variable MGMT expression values observed in MGMTunmethylated tumors (Fig.…”
Section: Regulation Of Expression and Function Of Mgmtmentioning
confidence: 99%
“…Recent studies addressed a further level of MGMT regulation through direct binding of specific miRNAs to the 3'-UTR of MGMT transcripts, which may lead to decreased mRNA stability and/or reduced protein translation [47]. Distinct miRNAs that have been implicated as direct regulators of MGMT expression include miR-181b [48,49], miR-181d [49], mir221/222 [50], as well as miR-767-3p and miR-648 [47]. Thus, also aberrant expression of miRNAs may contribute to the variable MGMT expression values observed in MGMTunmethylated tumors (Fig.…”
Section: Regulation Of Expression and Function Of Mgmtmentioning
confidence: 99%
“…Despite recent advances in treatment by a combination of surgery and chemotherapy and/ or radiotherapy, the prognosis of malignant glioma remains extremely poor. Glioblastoma (GBM) is the most common and malignant glioma, and has a median survival time of approximately one year (1)(2)(3)(4)(5)(6)(7). In the United States, 75% of glioma patients die within 5 years of diagnosis (8).…”
Section: Introductionmentioning
confidence: 99%
“…MiR-181b and miR-181c were significantly down-regulated in glioblastoma tissue of patients who responded to RT/TMZ in comparison to patients with progressive disease [183,185]. In a recent study by Zhang et al [186] genome-wide miRNA profiling of 82 glioblastomas demonstrated that miR-181d was inversely associated with patient overall survival and temozolomide (TMZ) treatment. Bioinformatics analysis of potential genes regulated by miR-181d revealed methyl-guanine-methyl-transferase (MGMT) as a downstream target.…”
Section: Micro-rna (Mirna) Dysregulationmentioning
confidence: 99%
“…Finally, there is still lack of miRNA delivery system with enough specificity and efficacy [183]. Telomerase ac va on by c-MYC over-expression [50] VEGFA over-expression [156] P53 inac va ng muta on AKT over-expression BAX dele on [34,65,74] Muta on: IDH1/2 LDHA silencing [120] MGMT down regula on by miR181d [186] IL10 NFKB dysregula on: NFKBIA dele on [62] PTEN regula on of IL10 and B7H1 expression [60,74] Ac va ng invasion…”
Section: Micro-rna (Mirna) Dysregulationmentioning
confidence: 99%